Definition of degree of participation of a chamois (rupicapra rupicapra)in formation of the natural focus of echinococcosis in the forest massifs of the North caucasus - B. M. Shipshev; F. I. Kishtikova; A. I. Tokhayeva; A. A. Tkhakakhova; I. H. Shakhbiyev; R. V. Bersanukayeva; H. H. Shakhbiyev; S. Sh. Mantayeva (Российский паразитологический журнал, 2016)
A chamois are infected with Echinococcus granulosus at 12,0% at detection on the average 6,0±0,4 cysts/goal. E. granulosus cysts had the small size. In a liv- er and lungs of a chamois at the same time 3,6±0,3 of fertile cysts and 2,4±0,2 cysts/goal of acephalocysts of E. granulosus are registered respectively. The number of protoscolexes in 1 ml of the liquid reached 43,6±5,3 sp. It was found more than 70 % fertile cysts of E. granulosus in lungs.